The Impact of Using Mining Technology on the Environment in the Manggarai Mine Circle Community From the Ethical Perspective of Hans Jonas - Hironimus Jesanto Tamat; Herman Flani Odang (Parahyangan Catholic University, 2022)
This paper focuses on the issue of the impact of the use of mining technology on the environment of the Manggarai mining circle community from the perspective of Hans Jonas responsibility ethics. Technological advances increasingly developing have a tangible impact on the entire order of human life. In addition to being very helpful to humans in everyday life, it turns out that the presence of technology negatively impacts humans, including the environment. The environment is often used as an object that provides satisfaction and benefits for humans, even so, many problems arise due to the transition of functions to nature to generate profits. The environment becomes threatened because it is polluted and damaged. The authors raised this issue using the literature method with the sources used in the form of literature from various books and journals. According to Hans Jonas, the findings of this paper are that the environment is the place and future of all living things, especially humans. Therefore, the living environment needs to be appropriately maintained, cared for, and preserved for the integrity of the existing creation and living in it.